Intraoperative Cerebral Angiography by Intravenous Contrast Administration With 3-Dimensional Rotational Fluoroscopy in Patients With Intracranial Aneurysms: A Feasibility Study. Issue 1 (16th January 2015) - Westermaier, Thomas; Linsenmann, Thomas; Keßler, Almuth F; Stetter, Christian; Willner, Nadine; Solymosi, Laszlo; Ernestus, Ralf-Ingo; Vince, Giles H
Abstract: BACKGROUND: Intraoperative imaging of cerebral aneurysms may be desirable in emergency situations with large space-occupying hematomas or to visualize vessels after clip placement. Mobile 3-dimensional fluoroscopes are available in a number of neurosurgical departments and may be useful in combination with simple image postprocessing to depict cerebral vessels. OBJECTIVE: To assess whether intracranial aneurysms are detectable with appropriate image quality with intraoperative 3-dimensional fluoroscopy with intravenous contrast administration. METHODS: Eight patients were included in the study. The patients' heads were fixed in a radiolucent Mayfield clamp. First, a rotational fluoroscopy scan was performed without contrast agent. Then, a second scan with 50 mL iodine contrast agent was performed. The DICOM (digital imaging and communications in medicine) data of both scans were transferred to an Apple PowerMac workstation, subtracted, and reconstructed with OsiriX imaging software. The images were compared with preoperative angiograms. RESULTS: No adverse effects were observed during contrast administration. The entire procedure from fluoroscope positioning to the production of usable 3-dimensional images took 5 to 6 minutes with an image acquisition time of 2 × 24 seconds. The configuration of the aneurysm and the vessel anatomy were assessable. Previous coiling limited image quality in 1 patient. CONCLUSION: This technique quickly provides images of adequate quality to assess the configuration of intracranial aneurysms, which may be helpful when immediate intraoperative information about intracranial vessel pathologies is required. The positioning of the fluoroscope, image acquisition, and processing can be completely integrated into the surgical workflow.